Faktor-Faktor yang Memengaruhi Pengungkapan Corporate Social Responsibility - Alit Ariawan, I Dewa Nyoman; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 30 No 10 (2020), 2020)
This research is an empirical study that aims to determine the effect of managerial ownership, leverage, profitability, and type of industry on the disclosure of Corporate Social Responsibility (CSR). The population uses all companies listed on the Indonesia Stock Exchange in 2018 and the sample is chosen using purposive sampling. Managerial ownership is measured by the percentage of shares owned by management. The level of leverage is measured by the debt ratio (DER). Profitability is measured by ROA, and industry types are grouped into high-profile and low-profile. CSR is measured by the CSR index, CSRDI. Data were tested for normality, multicollinearity, and heteroscedasticity. Data analysis uses multiple linear regression analysis techniques. The results indicate that managerial ownership has no effect on CSR disclosure. The level of leverage has a negative effect on CSR disclosure. Profitability has a positive effect on CSR disclosure. Industry type has no effect on CSR disclosure. Keywords: Leverage; Profitability; Industry Type; Corporate Social Responsibility.